Integrasi Kurikulum Pesantren dan Perguruan Tinggi - Muhammad Khoiruddin (Cendekia: Kependidikan dan Kemasyarakatan, 2019)
Abstract: Developments and changes were made to the boarding school, as part of the constellation of the modern world as well as adaptation, showing the life of the boarding school is no longer considered to be static and stagnant. The dynamics of the boarding school has been proven with the involvement and active participation to provide public services in many aspects of life that always accompanies it, among others, participated in making national life through educational institutions pesantren. because schools are educational institutions which have strong cultural roots in the community, Conventional learning systems and methodologies adopted schools generally range in variants such as sorogan, weton or bandongan, halaqah and recitation In the midst of failure in the education system today, we should listen back pesantren education system. The development of integration in the cognitive, affective, and psychomotor always proclaimed schools need attention.ملخص: إن التطورات والتغييرات التي تطرأ على المدارس الداخلية الإسلامية جزء لا يتجزأ من النظام العالمي الحديث، فتكيف عالمالمعهد الاسلامى يدل على أن ديناميكيات  المعهد الاسلامى لم تعد تعتبر راكدة وثابتة. الذي كان يرافقه دائمًا، من بين أمور أخرى، شارك في تشكيل الروح الوطنية من خلال مؤسسات التعليم المعهد الاسلامى. نظرًا لأن المعهد الاسلامى مؤسسات تعليمية لها جذور ثقافية قوية في المجتمع، فقد تم اعتماد أنظمة وأساليب التعلم التقليدية من المدارس العامة في أشكال مختلفة مثل مشافهة أو الحلقة العامة والحلقه والتعلم عن ظهر قلب، وهي الإجابة وسط الإخفاقات في نظام التعليم الحالي اليومى، يمكن تطوير تعليم المعهد الاسلامى بشكل احترافي كنموذج تطوير متكامل في المجالات المعرفية والعاطفية والنفسية حتى يتسنى دمج منهج  المعهد الاسلامى والمناهج الرسمية مع المثل الأعلى.